Acute Invasive Fungal Rhinosinusitis in Immunocompromised Patients: Role of an Early Diagnosis. (August 2018) - Fernandez, Ignacio Javier; Crocetta, Francesco Maria; Demattè, Marco; Farneti, Paolo; Stanzani, Marta; Lewis, Russel E.; Fornaciari, Martina; Pasquini, Ernesto; Sciarretta, Vittorio
Objective: The aims of the present study were to evaluate the clinical significance of the delay for surgical treatment and the prognostic value of other clinical, pathologic, and microbiological variables among hematologic patients affected by acute invasive fungal rhinosinusitis (AIFRS). Furthermore, we propose our early diagnosis and treatment protocol, reporting its 10-year results. Study Design: Monocentric retrospective analysis. Setting: The study was conducted from 2001 to 2017 at the University Hospital of Bologna, Italy. Subjects and Methods: The impact of time to treatment and clinical, pathologic, and microbiological variables were analyzed among patients with histologically and microbiologically proven AIFRS. The outcomes of patients treated before the introduction of the early diagnosis protocol were compared with those treated afterward. Results: Nineteen patients affected by AIFRS were eligible for the study. Treatment delay >4 days ( P = .002), infection caused by Mucorales ( P = .015), and extension of the disease were negative prognostic variables ( P = .017). The application of our protocol significantly reduced the delay for diagnosis and appropriate treatment by an average of 7.3 days ( P = .02). Conclusion: The promptness of the diagnosis and surgical treatment may play a significant role in the management of AIFRS, as it appears to be significantly associated with the disease outcome. Our protocol may help to reduce the time required for diagnosis of high-risk hematologic patients.